DELIBERASI PERENCANAAN PEMBANGUNAN DESA PETAI BARU KECAMATAN SINGINGI KABUPATEN KUANTAN SINGINGI TAHUN 2015-2016 - Ricky Pratama; Khairul Anwar (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
Deliberation of development planning is a process or way of involving individuals in making decisions in deliberations. The form of a new space for the success of the village planning meeting is the establishment of a deliberative forum, where citizens talk based on issues and needs that are based on people's knowledge and capacity. The purpose of the study was first, to find out how the deliberation process of hamlet meetings and the results of village hamlet mesrenbang. Second, to find out the musrenbang deliberation process and how to encourage community involvement in the process of developing village development planning. The location of this research was conducted by the New Petai Village. The type of research used is qualitative research methods. Data collection techniques are done by interviewing and observing.The results of the musrenbang research conducted by the Petai Baru Village are in accordance with the rules, namely through community meetings at the hamlet level and then towards the village planning meeting. However, deliberation in development planning here has not been carried out by the people of Petai Baru Village. This can be seen in the attendance list and proposals at the New Petai Village Musrenbang. Keywords: Community Involvement, Independence, Deliberation Decisions.